2021
DOI: 10.13057/biodiv/d221240
|View full text |Cite
|
Sign up to set email alerts
|

Floristic composition and species diversity in three habitat types of heath forest in Belitung Island, Indonesia

Abstract: Oktavia D, Pratiwi SD, Munawaroh S, Hikmat A, Hilwan I. 2021. Floristic composition and species diversity in three habitat types of heath forest in Belitung Island, Indonesia. Biodiversitas 22: 5555-5563. Exploring plant diversity, structure, and composition of vegetation in forest ecosystems is necessary for understanding the mechanism of species coexistence and forest dynamics, moreover in a unique and vulnerable ecosystem such as tropical heath forest (kerangas). We investigated the composition and structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 39 publications
5
24
0
Order By: Relevance
“…In general, the species richness index in the kabun buah area had a higher value than that in the balukar anum and jurungan. This is similar to the research on heath forests on Belitung Island by Oktavia et al (2021) which states disturbances cause a low value of species richness across vegetation levels. The number of individuals of each species greatly affects the value of the richness index.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In general, the species richness index in the kabun buah area had a higher value than that in the balukar anum and jurungan. This is similar to the research on heath forests on Belitung Island by Oktavia et al (2021) which states disturbances cause a low value of species richness across vegetation levels. The number of individuals of each species greatly affects the value of the richness index.…”
Section: Discussionsupporting
confidence: 89%
“…The fallow land with the age of 7-12 years allowed some pioneer vegetation to grow. The species number at pole level in the jurungan was the highest which is similar to the research of Oktavia et al (2021) which stated that more species at pole levels were found than at seedling levels in the bebak area, which was a former cultivation area. In kabun buah with the age of 15 years or more, the species number was decreased.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Here we focussed on a tropical heath forest in Borneo, this forest type is found throughout the tropics and is characterized by a unique tree species composition (Fine et al, 2010;Newbery, 1991;Oktavia et al, 2021). Trees in heath forests have low productivity (Miyamoto et al, 2007(Miyamoto et al, , 2016, and leaves with low element concentrations (Aoyagi & Kitayama, 2015;Luizão et al, 2004;Peace & Macdonald, 1981;Turner et al, 2000).…”
Section: Introductionmentioning
confidence: 99%